1999
DOI: 10.3109/08923979909007122
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Determinants of Modified Cobra Venom Neurotoxin Which Induce Immune Resistance to Experimental Allergic Encephalomyelitis: Molecular Mechans for Immunologic Action

Abstract: A nontoxic, iodoacetamide-modified cobratoxin derivative (CAM-NTX) induced resistance to experimental allergic encephalomyelitis (EAE) in guinea pigs. Resistance was retained after trypsin digestion and shown to reside in N-terminal and central peptides of CAM-NTX. A similarly modified protein cardiotoxin (CAM-CTX), representative of proteins homologous with cobratoxin, was not immunosuppressive. Depressed clinical symptoms in EAE-resistant animals correlated with reduced lymphocytic infiltration of the brain.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Previous studies showed that in the presence of complement, activated microglia showed significant phagocytosis of myelin basic protein in vitro [Zajicek et al, 1992], and strong expression of CD59 (a complement regulatory protein molecule) occurs was observed in areas of myelin production [Zajicek et al, 1995]. Complement activator cobra venom factor (CVF) treatment had been used to reduce serum complement in MBP‐induced EAE and caused suppression of disease [Pabst et al, 1971; Linington et al, 1989; Hinman et al, 1999]. Although complement activation is not specific to MS, the complement activation in active MS may indicate initial myelin attack, assessed in combination with other inflammatory and immune markers, may be of value as biomarkers in the early stage of MS.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that in the presence of complement, activated microglia showed significant phagocytosis of myelin basic protein in vitro [Zajicek et al, 1992], and strong expression of CD59 (a complement regulatory protein molecule) occurs was observed in areas of myelin production [Zajicek et al, 1995]. Complement activator cobra venom factor (CVF) treatment had been used to reduce serum complement in MBP‐induced EAE and caused suppression of disease [Pabst et al, 1971; Linington et al, 1989; Hinman et al, 1999]. Although complement activation is not specific to MS, the complement activation in active MS may indicate initial myelin attack, assessed in combination with other inflammatory and immune markers, may be of value as biomarkers in the early stage of MS.…”
Section: Discussionmentioning
confidence: 99%
“…The first studies to examine the role of C in EAE used the C activator cobra venom factor (CVF) as a treatment to reduce serum C, reducing the severity of EAE markedly [45–48]. Despite initial success, it was soon realized that response to this treatment was transient and repeated injections were highly immunogenic; further, CVF‐induced C activation led to production of vast quantities of the proinflammatory anaphylatoxins C3a and C5a, sufficient to cause a shock syndrome in recipients.…”
Section: Complement In Ms – Animal Modelsmentioning
confidence: 99%
“…Also, bee venom (from Apis mellifera ) was found to ameliorate disease symptoms, improve motor function and reduce inflammatory markers [reviewed in 2]. Even snake venoms were found to play a vital role in MS therapy by inhibition of clinical signs of autoimmune encephalomyelitis and lymphocyte brain infiltration [132,133]. New molecules derived from the venom of Thalassophryne nattereri Brazilian fish, so called TnP family, generate systemic and CNS specific effects that result in inhibition of inflammatory leukocyte migration to CNS and demyelination and thus could be a therapeutic opportunity for the treatment of MS [134].…”
Section: Efficacy Of Various Drugs In Ms Patientsmentioning
confidence: 99%